In situ growth of Fe(ii)-MOF-74 nanoarrays on nickel foam as an efficient electrocatalytic electrode for water oxidation: a mechanistic study on valence engineering. Issue 75 (3rd September 2019) - Wang, Qijun; Wei, Feifei; Manoj, Devaraj; Zhang, Zheye; Xiao, Junwu; Zhao, Xuezhu; Xiao, Fei; Wang, Hairen; Wang, Shuai
Abstract : DFT results first demonstrate that varying the metal valence can tune the stable intrinsic electronic structure of MOF, different valence Fe(ii ) and Fe(iii )-MOF-74 nanoarrrays on nickel foam are further synthesized as electrode for water oxidation. Abstract : In this work, our theoretical results first demonstrate that varying the metal valence in MOFs plays a significant role in tuning their stable intrinsic electronic structure. Different valence Fe(ii ) and Fe(iii ) based pristine MOF-74 nanoarrays on nickel foam are further synthesized as electrodes for highly efficient electrocatalytic water oxidation.